2020
DOI: 10.1002/pol.20190076
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model Metallo‐Supramolecular Dual‐Network Hydrogels with Independently Tunable Network Crosslinks

Abstract: Hybrid polymer networks emerge between chemical and physical crosslinking, where two different modes of chain connectivity control the material behavior. However, rational relations between their microstructural characteristics, supramolecular kinetics, and the resulting network mechanics and dynamics are not well developed. To address this shortcoming, this study introduces a material platform based on a model dual-network hydrogel, comprising independently tunable chemical and physical crosslinks. The idea i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…Further on, we investigated the hydrogel formation upon addition of stronger complexing Ni 2+ ions (Figure 4B, ) which form the most kinetically inert complexes with average dissociation times in the range of hours (log( k ass ) = 3.1, log( k dis ) = −7.6, log K = 21.8). [ 55 ] Due to the high association constant, reversible polymer networks cross‐linked by bis(Tpy)‐Ni 2+ complexes show purely elastic behavior at room temperature [ 57 ] and typical network relaxation times measurable by stress relaxation experiments at elevated temperatures (70 °C) comprise more than 15 h. [ 58 ] However, in the present study, a lower plateau modulus but similar LVE regime was observed in comparison to the Fe 2+ and Zn 2+ cross‐linked gels. The nanostructural investigation of the Ni 2+ cross‐linked nanorods via TEM revealed not only a decrease in the average length compared to the other metal ion treated samples (Fe 2+ : L n = 47 ± 20 nm; Zn 2+: L n = 53 ± 24 nm; Ni 2+ : L n = 27 ±10 nm), but also a significantly increased number of clusters (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further on, we investigated the hydrogel formation upon addition of stronger complexing Ni 2+ ions (Figure 4B, ) which form the most kinetically inert complexes with average dissociation times in the range of hours (log( k ass ) = 3.1, log( k dis ) = −7.6, log K = 21.8). [ 55 ] Due to the high association constant, reversible polymer networks cross‐linked by bis(Tpy)‐Ni 2+ complexes show purely elastic behavior at room temperature [ 57 ] and typical network relaxation times measurable by stress relaxation experiments at elevated temperatures (70 °C) comprise more than 15 h. [ 58 ] However, in the present study, a lower plateau modulus but similar LVE regime was observed in comparison to the Fe 2+ and Zn 2+ cross‐linked gels. The nanostructural investigation of the Ni 2+ cross‐linked nanorods via TEM revealed not only a decrease in the average length compared to the other metal ion treated samples (Fe 2+ : L n = 47 ± 20 nm; Zn 2+: L n = 53 ± 24 nm; Ni 2+ : L n = 27 ±10 nm), but also a significantly increased number of clusters (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Further on, we investigated the hydrogel formation upon addition of stronger complexing Ni 2+ ions (Figure 4B, ) which form the most kinetically inert complexes with average dissociation times in the range of hours (log(k ass ) = 3.1, log(k dis ) = −7.6, log K = 21.8). [55] Due to the high association constant, reversible polymer networks cross-linked by bis(Tpy)-Ni 2+ complexes show purely elastic behavior at room temperature [57] and typical network relaxation times measurable by stress relaxation experiments at elevated temperatures (70 °C) comprise more than Step strain measurements (same color code as before) (M 2+ :Tpy = 1:2 if not indicated otherwise, 𝜔 = 1 rad s −1 ), H 2 O, 20 °C, G′: full symbols, G″: empty symbols). Note, that all metal ions were added in form of their respective triflate salts.…”
Section: Resultsmentioning
confidence: 99%
“…While the frequency dependence of G’ is clear and qualitatively similar to that of the Ni-based gel, we did not observe a peak in loss modulus, which could have been associated with the lifetime of the physical bonds. This result suggested that the physical bond breaking and chain relaxation occurred at much higher frequencies [ 13 , 18 , 25 ], which indicated a much shorter lifetime for the Zn 2+ –imidazole bond than that for the Ni 2+ –imidazole bond. At low frequencies, the values of G ’ approached those of the chemical gel.…”
Section: Resultsmentioning
confidence: 99%
“…However, in supramolecular polymers, the enhanced polymeric dynamics of longer chains can overcome the association tendency of supramolecular units and thereby decrease the extent of phase-separation. 90,91 Moreover, in supramolecular polymeric hydrogels, the polar polymer precursor is responsible for assuring the system's solubility, which undermines the phase-segregation affinity of the supramolecular units. 80 Therefore, the effect of the polymer core length and incompatibility on enhancing the aggregation of associative motifs can be compromised by the enhanced polymeric dynamics and the increased solubility, respectively.…”
Section: Hierarchical Assembly Into Ordered Structuresmentioning
confidence: 99%